The Politics of Decolonisation and Bi-Nationalism in Israel/Palestine. (May 2019) - Bashir, Bashir; Busbridge, Rachel
Recent years have seen a revitalisation of decolonisation as a framework of analysis in the Israeli–Palestinian conflict. This article maps changes in the meanings attached to decolonisation in the Israeli Israeli–Palestinian context, paying particular attention to the one-state paradigm. One-state proposals highlight bi-national realities in historic Palestine in order to lay out a decolonising vision grounded in equal civic rights. Many one-state advocates, however, are suspicious of a prescriptive bi-national paradigm that would afford the two national groups equal collective rights, primarily because its recognition of Jewish national self-determination is seen as entrenching, rather than decolonising, colonial relations of power. We argue that a prescriptive bi-nationalism in fact offers rich resources for a decolonising project in Israel/Palestine that seeks to establish a polity based on the principles of justice and equality – come to terms with historical injustice and imagine alternative pasts, presents and futures based on Arab–Jewish relationships.